The association between dietary inflammatory index, dietary antioxidant index, and mental health in adolescent girls: an analytical study - Parvin Dehghan; Marzieh Nejati; Farhad Vahid; Amir Almasi-Hashiani; Sevda Saleh-Ghadimi; Reza Parsi; Hamed Jafari-Vayghan; Nitin Shivappa; James R. Hébert (BMC, 2022)
Abstract Background Diet is considered as one of the modifiable factors that appears to exert a vital role in psychological status. In this way, we designed this study to examine the association between dietary inflammatory index (DII), dietary antioxidant index (DAI), and mental health in female adolescents. Methods This cross-sectional study included 364 female adolescents selected from high schools in the five regions of Tabriz, Iran. A 3-day food record was used to extract the dietary data and calculate DII/DAI scores. DII and DAI were estimated to assess the odds of depression, anxiety, and stress based on the Depression Anxiety Stress Scales-21. Adjusted relationships of the DII and DAI with depression, anxiety, and stress were determined using multiple regression after adjusting for age, energy intake, BMI, family income and mother and father education. Overweight was defined as body mass index (BMI)-for-age >  + 1 z-score relative to world health organization standards. Results Depression, anxiety, and stress were observed in 21.4%, 26.6%, and 25.7% of subjects, respectively. The percentage of overweight among adolescents was 19.4%. The association between DII and score of mental health profile was positive among subjects in the third tertile of DII compared to subjects in the first tertile. However, this association was not statistically significant after adjusting for confounding variables. Moreover, there was a significant inverse association between DAI and depression and anxiety; and a statistically insignificant association between DAI and stress after adjusting for confounders. Conclusions Our results highlighted the importance of a healthy and anti-inflammatory diet on mental health in female adolescents. Therefore, modifying unhealthy dietary habits are likely to be effective in the management of psychosocial disorders.